Superman, the one who fell - Johnson, Phillip Kennedy (DC Comics, 2021)
"Phillip Kennedy Johnson jumps from Future State and brings the Kents back to the present, crafting a father-son story that spans both Superman and Action Comics! In "The Golden Age" Jonathan Kent is back from the 31st century and fighting cosmic threats alongside his legendary father, Clark Kent. But when an interdimensional breach opens near Earth, Jon recognizes the creatures that emerge: the cosmic leviathans that the Legion of Super-Heroes credits with the death of Superman! As Superboy desperately tries to save Superman's life from the leviathans of the breach, Superman discovers the breach's shocking origins. But with his powers mysteriously fading, he is utterly outmatched. Can Superboy change the course of history and save his father's life?"--
"Superman created by Jerry Siegel and Joe Shuster. Superboy created by Jerry Siegel. By special arrangement with the Jerry Siegel family.
"Originally published in single magazine form in Superman 29-32, Action Comics 1029."--Title page verso
Keywords: Superman -- Fiktive Gestalt; Comic